2023
DOI: 10.1128/spectrum.04827-22
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-Independent SARS-CoV-2 Infection in Pulmonary Epithelial Cells

Abstract: The development of inhibitors of the SARS-CoV-2 infection remains a need of utmost importance. The Wnt signaling pathway in host cells is often implicated in infections by bacteria and viruses. In this work, we show that, despite previous indications, pharmacological modulation of the Wnt pathway does not represent a promising strategy to control SARS-CoV-2 infection in lung epithelia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Chatterjee et al were the first to demonstrate the role of β-catenin in SARS-CoV-2 infection by iCRT-14 treatment and β-catenin silencing in Vero cells, which have both effectively reduced virus infection [ 17 ]. On the other hand, Koval et al had tested several Wnt inhibitors, namely clofazimine, MU17, F2-99 and ICG-001, in Calu-3 and A549-ACE2-TMPRSS2 cells and have shown no significant inhibition in SARS-CoV-2 infection, hence contradicting the initial observations of the possible role of the canonical signaling pathway for SARS-CoV-2 infection [ 18 ]. Nonetheless, our findings agree with those of Chatterjee et al that the canonical Wnt signaling pathway is important for SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chatterjee et al were the first to demonstrate the role of β-catenin in SARS-CoV-2 infection by iCRT-14 treatment and β-catenin silencing in Vero cells, which have both effectively reduced virus infection [ 17 ]. On the other hand, Koval et al had tested several Wnt inhibitors, namely clofazimine, MU17, F2-99 and ICG-001, in Calu-3 and A549-ACE2-TMPRSS2 cells and have shown no significant inhibition in SARS-CoV-2 infection, hence contradicting the initial observations of the possible role of the canonical signaling pathway for SARS-CoV-2 infection [ 18 ]. Nonetheless, our findings agree with those of Chatterjee et al that the canonical Wnt signaling pathway is important for SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 98%
“…Wnt3a has been studied in several viruses, such as influenza virus, Rift Valley Fever virus (RVFV) and pseudorabies virus [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, conflicting studies made the involvement of Wnt in SARS-CoV-2 infection inconclusive [ 17 , 18 ]. Chatterjee et al showed that silencing β-catenin expression and inhibiting its activity reduced virus infection [ 17 ], whereas Koval et al demonstrated that the addition of several Wnt inhibitors has no effect on SARS-CoV-2 infection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation